Molecular and phylogenetic analysis of zoonotic Plasmodium in long-tailed macaques: insights from wildlife-human conflict zones in Selangor, Malaysia - Zamri, Safawati Zawani; Abdul Aziz, Nor Azlina; Mazlan, Mazlina; Saidu, Yaro Sallau; Zulhisam, Atiqah; Che-Amat, Azlan; Sipin, Quincie (Springer, 2025)
A cross-sectional study was conducted to assess the prevalence, genetic diversity, and phylogenetic relationships of three zoonotic malaria parasites known as Plasmodium cynomolgi, P. inui, and P. knowlesi in long-tailed macaques (Macaca fascicularis) from wildlife-human conflict zones in Selangor, Malaysia. The study conducted between September 2022 and April 2023, involved N = 100 macaques culled as part of wildlife management programs in Petaling and Hulu Langat districts. Nested polymerase chain reaction (PCR) analysis revealed a prevalence of 24% for P. cynomolgi, 23% for P. inui, and 4% for P. knowlesi. Infection patterns included 51% single infections, 18% dual infections, and 2% triple infections. Phylogenetic analyses were performed using the Maximum Likelihood method with the Kimura 2-parameter model and 1,000 bootstrap replicates. Results identified major lineages (S-type and A-type) for all three Plasmodium species, providing insights into their evolutionary relationships and host-parasite interactions. The findings underscore the zoonotic potential of long-tailed macaques in wildlife-human conflict zones and emphasize the need for regular monitoring and surveillance to mitigate the public health risks associated with zoonotic malaria.